Pengaruh Intensitas Membaca Al-Quran Terhadap Kecerdasan Emosional Mahasiswa Psikologi Angkatan 2023 Universitas Islam Negeri Sunan Gunung Djati Bandung - zahrafi, kayla nazwa; Rohman, Ujang; Ismail, Shalahudin (UIN Sunan Gunung Djati Bandung, 2025)
The purpose of this study is to describe how much the intensity of reading the Quran affects the emotional intelligence of psychology students class of 2023 of Sunan Gunung Djati State Islamic University, Bandung. The research used is the result of reading the Quran on the emotional intelligence of students who have four different scales, namely strongly agree, agree, disagree, and strongly disagree. By using the instrument used in this study, namely using a google form questionnaire about the intensity of reading the Quran on students' emotional intelligence by seeing how much influence it has. The data analysis technique used was drawing conclusions and presenting non-probability sampling data with the type of purposive sampling used for 60 students. The results of the data analysis can find out how much percentage of aspects are fulfilled from the influence of the intensity of reading the Quran with the emotional intelligence of each student.